Counselor educators’ perceptions of the preparation of school counselors for advocacy - Kircher, Robert L. (Kansas State University, 2007)
Advocacy is an increasingly integral role for school counselors, and advocacy dispositions, knowledge, and skill competencies are critical for school counselors to function effectively in the contemporary school setting. This study assessed the perceptions of school counselor educators regarding the degree of importance of including advocacy dispositions, knowledge, and skill competencies (Trusty & Brown, 2005) in master’s degree school counseling programs; the extent to which the advocacy competencies are taught in the program; and the relative readiness of program graduates to apply the advocacy competencies. Additionally, this study also investigated whether there were significant differences between the responses of participants associated with CACREP-accredited and those with non-CACREP-accredited school counselor preparation programs. Stratified proportional sampling was used to identify study participants. A sample of 250 counselor educators teaching in master’s degree programs in school counseling was identified and a survey was sent to each participant. One-hundred thirty six surveys were returned (54.4%); this represented 69 CACREP-accredited programs and 67 non-CACREP-accredited programs involving respondents in each region of Association for Counselor Education and Supervision. Mean ratings for respondents indicated that counselor educators perceived inclusion of the 15 advocacy competencies in master’s programs in school counseling as moderately to very important, moderately taught in their programs, and their graduates to be moderately ready to apply the advocacy competencies. Using independent samples t-tests to compare the mean ratings, the results showed no statistically significant differences between CACREP-accredited and non-CACREP-accredited respondents. It was concluded that the advocacy disposition, knowledge, and skill competencies delineated by Trusty and Brown (2005) are appropriate for inclusion in master’s degree programs in school counseling, and that additional focus on advocacy competencies might be needed within programs to ensure that all school counseling graduates learn and are able to apply the competencies. It was also concluded that the perceptions of counselor educators in CACREP-accredited and non-CACREP-accredited programs are more similar than different relative to the importance of including the competencies in graduate programs, the extent to which they are taught, and the readiness of graduates to apply the competencies.
Keywords: School counseling; Counselor role as advocate; Advocacy skills; Counselor education; Professional competencies for advocacy; Council for Accreditation of Counseling and Related Educational Programs; Education, Guidance and Counseling (0519)